The complete spectrum of pentalogy of Cantrell in one of a set of dizygotic twins: A case report of a rare congenital anomaly. Issue 14 (9th April 2021) - Zvizdic, Zlatan; Sefic-Pasic, Irmina; Mesic, Amira; Terzic, Sabina; Vranic, Semir
Abstract: Rationale: Pentalogy of Cantrell (POC) is an extremely rare syndrome with an estimated incidence of 1:65, 000 to 200, 000 live births. Its complete form includes a midline epigastric abdominal wall defect, defects affecting the lower sternum, anterior diaphragm, diaphragmatic pericardium, and various intracardiac defects. Patient concerns: We report a case of complete POC affecting only the first-born of a set of premature dizygotic twins. Diagnosis: A giant omphalocele with an eviscerated liver and bowel on prenatal, obstetric ultrasonography at 24 gestational weeks was observed. At birth, physical examination confirmed a massive (10 × 8 cm) epigastric omphalocele in which a significant part of the liver was seen. A postnatal echocardiogram revealed the presence of an ostium secundum atrial septal defect, perimembranous ventricular septal defect, and moderate pulmonary stenosis. X-ray showed an abnormal intrathoracic positioned stomach, which was confirmed with a plain x-ray of the upper intestinal tract with hydrosoluble contrast. Computed tomography (CT) scan revealed the sternum's absence and a close connection between the pericardial sac and the stomach wall. Interventions: The patient underwent surgical intervention at 18 days of age. Outcomes: Despite adequate and appropriate postoperative treatment, the baby rapidly deteriorated and died 72 hours after surgery. Lessons: POC is a complex, high-mortality syndrome whose management requires a multidisciplinary approach and meticulous planning. Despite all efforts, POC carries a poor prognosis, particularly in patients affected by its complete form.